Effect of Liquid Biofertilizer Concentration and Vermi-Comvost on Growth and Yield of Pakcoy (Brassica rapa L.) Plants - Fathony, Achmad; Abdullah, Rohana; Mulyana, Hudaya (Agripreneur : Jurnal Pertanian Agribisnis, 2022)
This research aims to study the effect of the interaction of different concentrations of extragene biofertilizer and different doses of vermicompost on the growth and yield of pakcoy plants, and wants to know the optimum concentration of extragen biofertilizer and the dose of vermicompost that gives the best results on pakcoy plants. The experiment was carried out in Cisondari Village, Pasirjambu District, Bandung Regency, West Java Province. with an altitude of 1200 meters above sea level, Latosol soil type with a pH of 6.21 (slightly acidic). The experimental design used a factorial Randomized Block Design (RAK) consisting of two factors and repeated twice. The first factor is the concentration of extragenic biological fertilizer (e) which consists of four levels, namely: e0 = control (0 ml/liter); e1 = extragen (3 ml/liter); e2 = extragen (6 ml/liter) and e3 = extragen (9 ml/liter). Vermicompost fertilizer dosage (K) consists of 4 levels, namely: k0 = Control (0 g/polybag); k1 = 16 g/polybag; k2 = 32 g /polybag and k3 = 48 g/polybag). The results of this research are: 1). By administering the highest dose of extragen liquid biological fertilizer of 9 ml/liter, results showed significantly different results in the height parameters of plants aged 21 HST. 2). Giving the highest dose of vermicompost fertilizer (0 gr/polybag) showed significantly different results. 3). In the combination treatment of extragen liquid biological fertilizer and vermicompost fertilizer, no interaction occurred